Perancangan Strategi Periklanan Serta Desain Media Promosi Merek Klote pada Media Shopee - Lazarus Valens Eldiantino; Febiana Tania (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2024)
The purpose of this study is to analyze and design an advertising plan and strategy for the Klote brand. In the digital age and an increasingly competitive business environment, advertising media plays a vital role in building brand awareness and reaching target audiences if the media is used properly. The research takes a qualitative approach, conducts interviews with founders and relevant sources, and analyzes consumer and market behavior. The results provide detailed insight into the preferences and characteristics of Klote's target audience, as well as the factors that influence the effectiveness of his Shopee homepage as an advertising vehicle. Based on these findings, appropriate planning and design strategies for advertising materials are developed, from media selection to formulating appropriate messages. The study should organize the structure, present the brand and product, and provide information about the product from the design created so that the advertising strategy and the planned concept can work together and support each other. Especially since he has a shop by Klote himself. The Shopee platform setup still needs to be revised in terms of advertising strategy and concept.